Analisis Persediaan Material Jenis Botol Menggunakan Metode Economic Order Quantity (EOQ) - Sofyan, Diana Khairani; Meutia, Sri (Universitas Teuku Umar, 2016)
Inventories have an important role in business operations. In fact, problems in controlling inventory is the most important thing we've come across in any company. Inventories have enormous influence for a smooth production process. PT Ima Montaz Sejahtera (PT IMS) is one of the companies engaged in the manufacture beverage Bottled Drinking Water. PT IMS is distributes its products throughout NAD. The main raw material used was water purchased from PT. PIM. The company ordered a bottle of the product medium, glass cup on products, lids, labels and cartons were booked from Medan which become relationship with them. But in reality, the bottle material is not always available because raw material ordering is not efficient, thus inhibiting the production process and increase the use of cost. In the years 2015-2016 from September to August happens 18 times a monthly ordered are ordering frequency from 1 to 2 orders with the amount of raw materials that different every month. Based on preliminary research shows that ordered data in September, October, November, December, January and February each performed two times ordered, while March, April, May, June, July and August each time is 1 ordered. Additionally in 2015 there were eight times the idle time in the production department Bottleline due to the absence of Safety Stock thus automatically no production activities in the production department Bottleline to incur losses for the company. Based on this it needs to be analyzed at the company's inventory control. The results showed that the frequency of the purchasing of raw materials by using the EOQ method which is 3 times the total cost of supply of raw materials companies amounted to Rp12,041,404. Where the company must hold safety stock to expedite the process of production by the number of 407.685 bottles, with reorder point of 362.961 bottles.Keywords: Inventory, Economic Order Quantity (EOQ), Reorder Point, Safety stock